New insights into N6-methyladenosine in hepatocellular carcinoma immunotherapy - Li, Mengran; Tian, Hu; Zhuang, Yanshuang; Zhang, Zili (Frontiers in Immunology, 2025)
N6-methylation is a modification in which a methyl group is added to the adenine base of a nucleotide. This modification is crucial for controlling important functions that are vital for gene expression, including mRNA splicing, stability, and translation. Due to its intricate participation in both normal cellular processes and the course of disease, as well as its critical role in determining cell fate, N6-methyladenosine (m6A) alteration has recently attracted a lot of interest. The formation and progression of many diseases, especially cancer, can be attributed to dysregulated m6A alteration, which can cause disturbances in a variety of cellular functions, such as immunological responses, cell proliferation, and differentiation. In this study, we examine how m6A dysregulation affects hepatocellular carcinoma (HCC), with a particular emphasis on how it contributes to immunological evasion and carcinogenesis. We also investigate its potential as a novel therapeutic target, providing new perspectives on potential therapeutic approaches meant to enhance clinical results for patients with HCC.